Transposon mutagenesis and cloning analysis of the pathways for degradation of 2,4-dichlorophenoxyacetic acid and 3-chlorobenzoate in Alcaligenes eutrophus JMP134(pJP4). - Don, R H (1985)
Plasmid pJP4 permits its host bacterium, strain JMP134, to degrade and utilize as sole sources of carbon and energy 3-chlorobenzoate and 2,4-dichlorophenoxyacetic acid (R. H. Don and J. M. Pemberton, J. Bacteriol. 145:681-686, 1981). Mutagenesis of pJP4 by transposons Tn5 and Tn1771 enabled localization of five genes for enzymes involved in these catabolic pathways. Four of the genes, tfdB, tfdC, tfdD, and tfdE, encoded 2,4-dichlorophenol hydroxylase, dichlorocatechol 1,2-dioxygenase, chloromuconate cycloisomerase, and chlorodienelactone hydrolase, respectively. No function has been assigned to the fifth gene, tfdF, although it may encode a trans-chlorodiene-lactone isomerase. Inactivation of genes tfdC, tfdD, and tfdE, which encode the transformation of dichlorocatechol to chloromaleylacetic acid, prevented host strain JMP134 from degrading both 3-chlorobenzoate and 2,4-dichlorophenoxyacetic acid, which indicates that the pathways for these two substrates utilize common enzymes for the dissimilation of chlorocatechols. Studies with cloned catabolic genes from pJP4 indicated that whereas all essential steps in the degradation of 2,4-dichlorophenoxyacetic acid are plasmid encoded, the conversion of 3-chlorobenzoate to chlorocatechol is specified by chromosomal genes.